Extravascular manifestations of Takayasu arteritis: focusing on the features shared with spondyloarthritis - Oh Chan Kwon; Sang-Won Lee; Yong-Beom Park; Ji Seon Oh; Sang Hoon Lee; Seokchan Hong; Chang-Keun Lee; Bin Yoo; Yong-Gil Kim (Arthritis Research & Therapy, 2018)
Abstract Background Takayasu arteritis (TAK) is a systemic disease characterized by large vessel involvement. Although the vascular characteristics of TAK are well characterized, there is no well-organized study demonstrating the extravascular manifestations of TAK. We aimed to evaluate the characteristics of extravascular manifestations of TAK, and to identify the association between vascular and extravascular manifestations of TAK. Methods TAK patients from two independent cohorts between January 2012 and October 2017 were included in the study. Patient characteristics were retrospectively collected from the electronic dataset. The computed tomography scans of all subjects were reviewed to evaluate the pattern of vascular involvement and presence of sacroiliitis. Clinical findings including uveitis, skin lesions, oral ulcers, arthritis, and inflammatory bowel disease (IBD) were reviewed. Logistic regression analysis was performed to evaluate the association between vascular and extravascular manifestations. Results For the 268 TAK patients, the mean age at diagnosis was 41.2 ± 14.2 years and 88.1% were female. The extravascular manifestation of TAK was observed in 19.0% of patients, the most common being arthritis including sacroiliitis (11.9%) followed by recurrent oral ulcers (8.6%) and IBD (2.6%). A multivariate logistic regression analysis revealed type IIB vascular involvement (adjusted odds ratio (OR) 2.956, 95% confidence interval (CI) 1.337–6.537, p = 0.007) and the erythrocyte sedimentation rate (ESR) (adjusted OR 1.014, 95% CI 1.003–1.025, p = 0.012) as significantly associated with the presence of axial and peripheral arthritis. Conclusions Extravascular manifestations of TAK were observed in up to one-fifth of patients. The most common extravascular manifestation was arthritis, which was associated with a type IIB vascular involvement pattern and a high ESR.